Soil coverage and nutrient accumulation by pinto peanut - Perin, Adriano; Guerra, José Guilherme Marinho; Teixeira, Marcelo Grandi (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to determine the rate of soil coverage, biomass yield and total accumulation of N, P and K in the aerial biomass of the legume Arachis pintoi Krapov. & W.C. Greg. The experimental design was a randomized block with four replicates arranged in a 2x4 factorial with two levels of row spacing (25 and 50 cm between rows) and four different planting densities (2, 4, 8 and 16 plants/m). Complete soil coverage was achieved 224 days after planting. Planting density affected the rate of soil coverage and the rate of dry matter and nutrient accumulation by the shoot tissue of the legume, but these parameters were not significantly affected by row spacing. The results suggest that the optimum planting density was 8 plants/m in rows spaced 50 cm apart.